Hormonal responses to taekwondo fighting simulation versus conventional resistance exercise in young elite taekwondo athletes. - Kim, E.; Singh, H.; Oh, H.; Kim, J.; Kim, Y.; Lim, S.; Kim, B. (Archives of Budo, 2019)
Background and Study Aim: Taekwondo, including martial art competitions, involve explosive and quick movements of the lower extremities and thus, require a high contribution of the anaerobic energy system. Previous findings indicate preferential use of anaerobic or lactic acid system in taekwondo including martial art competitions. The aim of this study was the knowledge about hormonal such as insulin-like growth factor 1 (IGF-1), testosterone and cortisol responses between taekwondo fighting simulation (TFS) and traditional resistance exercise (RE) in elite taekwondo athletes.